How unobservable Bond Positions in Retirement Accounts affect Asset Allocation - Marcel Marekwica; Raimond H. Maurer (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2007)
Many tax-codes around the world allow for special taxable treatment of savings in retirement accounts. In particular, profits in retirement accounts are usually tax exempt which allow investors to increase an asset's return by holding it in such a retirement account. While the existing literature on asset location shows that risk-free bonds are usually the preferred asset to hold in a retirement account, we explain how the tax exemption of profits in retirement accounts affects private investors' asset allocation. We show that total final wealth can be decomposed into what the investor would have earned in a taxable account and what is due to the tax exemption of profits in the retirement account. The tax exemption of profits can thus be considered a tax-gift which is similar to an implicit bond holding. As this tax-gift's impact on total final wealth decreases over time, so does the investor's equity exposure.
Keywords: H24; G11; 330; asset location; asset allocation; tax-deferred accounts; tax exempt accounts; Portfolio-Management; Private Rentenversicherung; Steuerbegünstigung; Theorie